Aplikasi e-Arsip Berbasis Android untuk Guru dan Karyawan di Sekolah Menengah Kejuruan - Purnomo, Muhammad Ikhwannusyifa; Wibowo, Feri; Harjono, Harjono; Supriyono, Supriyono (UNIB Press, 2024)
Current technological developments have experienced very rapid developments. Its use is not only to help work in an agency or company but can also create accuracy, speed, and completeness. This also impacts an agency such as SMK Negeri 1 Purwokerto, which wants to utilize technology to manage archival documents in electronic form or electronic archives (e-Archives). E-Archives are a system for collecting and storing information in the form of electronic documents to make them easy to view, manage, find, and reuse. The need for an electronic archive management system is because the archive management process at the agency still uses manual methods by storing archival documents in physical form in a storage area. This method causes several problems with archival documents, such as loss, damage, and difficulty searching for documents. This problem requires a solution to overcome it, namely by building an Android-based application or system as an application for recording and managing archival documents. The development method used is the Software Development Life Cycle (SDLC) method with the waterfall model. The type of research carried out is research and development of the Research and Development method. The final result of this research is to produce a product in the form of an Android-based application for managing archival documents. This research was successfully carried out by referring to functionality testing, which was carried out using the Black Box Testing method.